Windmill - O'Dwyer, Simon, 1969- (1996)
"Solar windmills are the new green energy of the 21st century. Mainly situated on top of cliffs along the Victorian coastline to maximise wind capacity, they have created debate from residents and towns over the ugliness and invasiveness of the huge towers and the need to protect the pristine coastline with the benefit of cleaner energy. This photograph was made in two parts on the same roll of film. The first exposure of the landscape with the tower was made at at 10.00 pm under the light of the moon on a long time exposure. Exposing the girl using the car headlights made up the second part of the image. Photographed with a Nikon F5 camera."--Simon O'Dwyer.
Part of collection: Simon O'Dwyer collection of photographs.
Title supplied by photographer.
Also available online
Published in: The Age.
Keywords: Solar turbines -- Victoria -- Photographs